Fatigue verification of a railway bridge deck according to the EN1992-1-1 - Carlos Sousa (2010)
Railway bridges are subjected to important cyclic loads, which implies that thefatigue strength of these structures must be verified at the design stage. The EN1992-1-1provides a procedure for fatigue verification of concrete structures. Additional informationregarding the fatigue behaviour of railway bridges is given by the European codesEN1992-2 and EN1991-2. However, some specificities of the fatigue behaviour of thesestructures are not covered by these documents. This paper discusses such specificities andproposes a possible approach to be followed in the fatigue verification of railway bridgedecks. Some incoherencies in the design rules provided by the Eurocodes are alsodiscussed. Possible improvements of these standards are suggested.